Analisis Rasio Keuangan untuk Memprediksi Financial Distress pada PT Austen Jaya di Bandar Lampung - Irwandi Irwandi (Politeknik Negeri Lampung, 2022)
The purpose of this study was to predict financial distress using financial ratio analysis at PT AUSTEN JAYA in Bandar Lampung. The ratio analysis used is the current ratio, return on assets, and leverage. The research data used was obtained directly through interviews and equipped with financial reports for four years from 2018 to 2021. The research method used is descriptive method on the results of financial ratio analysis. Based on the results of the study, it was found that returns on assets decreased continuously from 10.05% in 2018 to 9.04% in 2019, and fell again in 2020 by 6.15%, and there was a slight increase in 2021 to 6.25%. This situation describes the prediction of the occurrence of financial distress in accordance with the results of previous studies that profitability affects the prediction of financial distress. Another thing that supports is the curent ratio which continues to decline on the other hand, the leverage continues to increase. This situation shows the existence of financial difficulties indicated by the company's inability to earn profits, difficulty paying obligations, and the company's financing is increasingly dependent on outside parties. It is hoped that the company will immediately take steps to improve its finances, especially be careful with debt and secondly, do efficiency seriously.